The role of long non-coding RNAs in the pathogenesis of hereditary diseases - Peter Sparber; Alexandra Filatova; Mira Khantemirova; Mikhail Skoblov (BMC, 2019)
Abstract Background Thousands of long non-coding RNA (lncRNA) genes are annotated in the human genome. Recent studies showed the key role of lncRNAs in a variety of fundamental cellular processes. Dysregulation of lncRNAs can drive tumorigenesis and they are now considered to be a promising therapeutic target in cancer. However, how lncRNAs contribute to the development of hereditary diseases in human is still mostly unknown. Results This review is focused on hereditary diseases in the pathogenesis of which long non-coding RNAs play an important role. Conclusions Fundamental research in the field of molecular genetics of lncRNA is necessary for a more complete understanding of their significance. Future research will help translate this knowledge into clinical practice which will not only lead to an increase in the diagnostic rate but also in the future can help with the development of etiotropic treatments for hereditary diseases.